THE EFFECT OF TOWEL CURL EXERCISE ON IMPROVING BALANCE IN CHILDREN WITH FLAT FOOT AGES 4-5 YEARS - Lailatuz Zaidah (Jurnal Ilmiah Fisioterapi, 2019)
ABSTRACT The ability of children to be able to carry out physical activities in a coordinated way is needed to train flexibility, balance, and agility, in increasing these components a good balance is needed in each individual. Balance is a bodily function that is vital for humans as well as the five senses. In this case the balance is supported by the musculoskeletal system and the fulcrum. One of the factors that can cause impaired balance in children is flat foot, flat foot is a condition where the arch of the foot is not visible from birth and is covered in fat tissue. In general, arches form since the first 5 years with an age range of 2-6 years. The purpose of this study is to determine the effect of towel curl exercise in improving balance in children aged 4-5 years. The research method uses quasi experiment research with pre and post test research designs comparing the value of the Balace Sixteen Test (BST) before and after the intervention. The sample in this study consisted of 13 children with flat foot conditions who were given towel curl exercise for 6 weeks with an intensity of 2 times a week. The results of the paired sample t-test analysis with p = 0.001 (p <0.05) means that there is an effect of Towel Curl exercise on the balance of flat foot children aged 4-5 years Keywords: Towel Curl Exercise, sixteen balance test, flat foot, balance